INFLAMMATION AND INCREASING H. PYLORI ANTIBODY TITERS IN ACUTE CORONARY SYNDROME - O. N. Pavlov (Российский кардиологический журнал, 2011)
The comparison of biochemical and immunological parameters of venous blood in patients with varying clinical course of coronary heart disease (CHD) demonstrated that systemic inflammation in acute coronary syndrome is associated with increased H. Pylori antibody titers.